PENGARUH ENTREPRENEURSHIP EDUCATION,ENTREPRENEURIAL SELF EFFICACY DAN ENTREPRENEURIAL ATTITUDE TERHADAP ENTREPRENEURIAL MINDSET - Putri, Ayu Novianti Kresna; Herdinata, Christian; Padmawidjaja, Liestya (Universitas Ciputra Surabaya, 2025)
The unemployment grade, Indonesia is still categorized high from year to year. High unemployment and low welfare in Indonesia are affected by employee termination, especially the process of industry that is affected from Covid-19 and Lack of job fill. the attempt that can be done is to do expection of working opportunity by being an Entrepreneur than has final result that can increase economic growth in Indonesia. In preparing that drivers to help economy to be more stable, government cooperate with educational institution that applies entrepreneurship education than has an important growth to prepare the student in creating entrepreneurial mindset. Ciputra University is one of the institutions that applies Entrepreneurship as a learning program and has a mission to increase the number of Entrepreneurs. The purpose of this riset is (1) to find out the effect of entrepreneurship education on entrepreneurial mindset (2) to find out the effect of entrepreneurial self-efficacy on entrepreneurial mindset (3) to find out the effect of entrepreneurial attitudes on entrepreneurial mindset. This type of research is quantitative by using SPSS 25 as an analysis instrument. The number of respondents that used in the riset is 150 respondents. The results of this riset showed that (1) entrepreneurship education affects significantly on entrepreneurial mindset (2) entrepreneurial self-efficacy does not affect significantly on entrepreneurial mindset (3) entrepreneurial attitude affects significantly on entrepreneurial mindset.